Assessing and Reporting the Adverse Effects of Antipsychotic Medication: A Systematic Review of Clinical Studies, and Prospective, Retrospective, and Cross-Sectional Research. Issue 1 (January 2016) - Longden, Eleanor; Read, John
Abstract : Objective: Adverse effects (AEs) of antipsychotic medication have important implications for patients and prescribers in terms of well-being, treatment adherence, and quality of life. This review summarizes strategies for collecting and reporting AE data across a representative literature sample to ascertain their rigor and comprehensiveness. Methods: A PsycINFO search, following preferred reporting items for systematic reviews and meta-analyses statement guidelines, was conducted in English-language journals (1980 to July 2014) using the following search string: (antipsychotic* or neuroleptic*) and (subjective effect or subjective experience or subjective response or subjective mental alterations or subjective tolerability OR subjective well-being or patient perspective or self-rated effects or adverse effects or side effects). Of 7825 articles, 384 were retained that reported quantified results for AEs of typical or atypical antipsychotics among transdiagnostic adult, adolescent, and child populations. Information extracted included: types of AEs reported, how AEs were assessed, assessment duration, assessment of the global impact of antipsychotic consumption on subjective patient wellbeing, and conflict of interest due to industry sponsorship. Results: Neurological, metabolic, and sedation-related cognitive effects were reported more systematically than affective, anticholinergic, autonomic, cutaneous, hormonal, miscellaneous, and nonsedative cognitive effects. The global impact of AEs on patient well-being was poorly assessed. Cross-sectional and prospective research designs yielded more comprehensive data about AE severity and prevalence than clinical or observational retrospective studies. Conclusions: The detection and classification of AEs can be improved through the use of standardized assessment instruments and consideration of the global impact on subjective patient wellbeing. Observational research can supplement information from clinical trials to improve the ecological validity of AE data.